Proceso civilizatorio, violencia y deportes de combate; revisión integradora del boxeo vs artes marciales mixtas. [Civilizing process, violence, and combat sports; integrative review of boxing and mixed martial arts]. - Diego G. Morales-Rosillo; Jorge L. Petro; Diego A. Bonilla (Ramón Cantó Alcaraz, 2019)
There seems to be a general tendency towards the idea that mixed martial arts (MMA) are more violent than boxing. A narrative review was carried out to analyze this phenomenon from a sociological and motor praxeological point of view; moreover, an integrative review approach was selected to assess randomized controlled trials, systematic reviews, and meta-analyzes, published between 2008 and 2018, where epidemiological evidence about the incidence of injuries in these sports was presented. Logical boolean operators were used in the search algorithm for PubMed/Medline ("boxing" and "mixed martial arts") while the manual search in Google Scholar was done with the term "boxing mixed martial arts". A total of 24 studies met the inclusion criteria and were analyzed in this article. The results showed that; i) from the perspective of motor praxeology, the generalized idea that is questioned in this review does not seem to be supported, that MMA are more violent than boxing, at least from the study of the sport configuration parameters; ii) from the paradigm of sociology / sports psychology, there are no differences in the typology of violence between both sports; and iii) an epidemiological comparison did not show evidence to support that MMA presents a higher rate of injury than boxing. The present review provides the necessary foundations to understand that an analysis of the sports field should be based on a multidisciplinary approach that includes sport sociology / psychology, motor praxeology and sports epidemiology, among other sciences.